Pendekatan Hermeneutika Filosofis Gadamer dalam Konflik Digital Knetz dan Seablings di Media Sosial - Maria Risa Puspitasari; Fitzerald Kennedy Sitorus (CV. ITTC INDONESIA, 2026)
media platform X following the Day6 concert in Kuala Lumpur (January 2026) demonstrates that K-pop fandom conflict represents a clash between two cultural horizons that mutually interpret each other through pre-existing prejudices. This study aims to understand how prejudice, historical experience, and identity negotiation operate in cross-cultural dialogue within digital spaces. The approach used is qualitative, grounded in Hans-Georg Gadamer's philosophical framework, particularly the concepts of prejudice (Vorurteil), effective history (Wirkungsgeschichte), and fusion of horizons (Horizontverschmelzung). Data were collected through a literature review of hermeneutics and digital communication studies, tracing public discourse on social media platform X, and cross-national news coverage (Korea, Malaysia, Indonesia, Philippines, Singapore). The analytical technique employed is interpretive discourse analysis using close reading, source triangulation, and peer debriefing to ensure hermeneutic validity. The findings reveal three main results. First, prejudice and the economic hierarchy between East Asia and Southeast Asia operate as horizons that direct both parties' interpretations. Second, the fusion of horizons does not occur symmetrically between Knetz and SEAblings; instead, it produces a fusion of horizons among Southeast Asian netizens through the solidarity of the hashtag #SEAblings. Third, the digital space of X reinforces polarization while simultaneously providing an arena for the formation of a new regional identity as a form of hermeneutic resistance.